Orientation to Screening and Treating Patients for Food Insecurity, The MOTHeRS Project - Updated 2022 - Kolasa, Kathryn M.; Smith, Brittany; Craven, Kay (My University, 2021)
This is the presentation/training for staff and volunteers participating in the screening for and treatment of food insecurity in the MOTHeRS project. These materials can be adapted for other clinical sites. This is an updated version of the slide set used in 2021. The 2022 version reflects changes in procedures as the program was implemented but does not change the content of the bags and handouts. These slides were also used in a recording made by Dr. Kolasa and Ms. Brittany Smith, hosted on the website of Eastern AHEC, for the duration of the project. The long slide set (45 slides) describes: 1) Why the MOTHeRS Project is distributing emergency food bags to pregnant women at high risk of food insecurity (Slides 4 to 6); 2) The emergency food bag contents and rationale for items included (Slides 7 to 14); 3) How to screen for food insecurity in the clinical setting, using two validated questions (Slides 15 to 18); 4) How to briefly counsel a pregnant woman who screens positive for food insecurity (Slide 19-23); 5) How the process of getting food from the Vidant Health-ECU Medical Food Pantry to eligible women will work at different practice locations participating in the program (Slides 24 to 28); 6) How to counsel the food bag recipient using MOTHeRS Project handouts (Slides 29 to 42).
The MOTHeRS Project was developed in 2020 with funding from the United Healthcare Foundation (UHF), ECU Physicians and the Departments of OB-GYN, Psychiatry and Family Medicine, to utilize NC-STeP - a statewide telepsychiatry program to bring multidisciplinary care to three community-based primary care obstetric clinics in Carteret, Duplin, and Chowan counties. The program continued to expand to other communities in 2022. Through this collaborative care model that includes the patient, nurse navigator, diabetes educator, behavioral health manager, primary obstetrician, MFM specialist, and a psychiatrist consultant, the MOTHeRS Project brings support and insights of specialty physicians to the identified practices. An additional component of this program is the Medical Food Pantry to include healthy food bags and tailored patient education to women with high risk pregnancies and food insecurity, living in rural areas. Separate entries in this repository include English and Spanish versions of The MOTHeRS' Project handouts, technical report and more. Additional information about this project is available at its website: https://medicine.ecu.edu/mothers-project. The authors are pleased to share these materials with others at no expense, please credit The MOTHeRS Project, Brody School of Medicine at East Carolina University. We would appreciate you telling us if/how you used these materials.
Keywords: MOTHeRS project; food insecurity; screening; nutrition; emergency food bag; pregnancy; medical food pantry